Association of Leg Bias with Bipedal Speed and Power in Developing Soccer Players. Issue 1 (February 2014) - Witkowski, Zbigniew; Lipecki, Krzysztof; Lyakh, Vladimir
The aim of this research was to determine whether there is any association between leg bias and bipedal locomotion in young male soccer players. 227 participants, members of a Polish football club, were tested. Leg dominancy and maximal specific power of each leg were recorded.